Teacher pedagogical knowledge on technology-enhanced mathematical creativity - Siswono, Tatag Yuli Eko; Rosyidi, Abdul Haris; Zulnaidi, Hutkemri; Hartono, Sugi; Kohar, Ahmad Wachidul; Sutrisno, Sutrisno; Kunafaah, Kunafaah (Edelweiss Applied Science and Technology, 2025)
This study aims to examine the extent to which junior high school teachers' pedagogical and technological knowledge, as well as their ability to integrate technology, influence the development of students' mathematical creativity. Technology integration is positioned as an intervening variable connecting teachers' knowledge with students' creative thinking. A quantitative research design was employed, utilizing Structural Equation Modeling–Partial Least Squares (SEM-PLS) to analyze the relationships among five latent variables. Data were collected through a 54-item questionnaire administered to 128 junior high school mathematics teachers, selected purposively from three school districts in East Java, Indonesia. The results show that teachers' pedagogical skills are positively influenced by technology integration (β = 0.198), suggesting that integrating technology can enhance pedagogical practices and promote students' mathematical creativity. The study concludes that teachers who are competent in integrating technology are more capable of designing meaningful learning activities that foster creative thinking. The practical implication is that professional development programs should not only strengthen teachers' pedagogical competence but also provide training on how to effectively integrate technology into classroom practices to support mathematical creativity.